Protective Mechanism of Acacia saligna Butanol Extract and Its Nano-Formulations against Ulcerative Colitis in Rats as Revealed via Biochemical and Metabolomic Assays - Heba M.I. Abdallah; Naglaa M. Ammar; Mohamed F. Abdelhameed; Abd El-Nasser G. El Gendy; Tamer I. M. Ragab; Ahmed M. Abd-ElGawad; Mohamed A. Farag; Mona S. Alwahibi; Abdelsamed I. Elshamy (Biology, 2020)
Ulcerative colitis (UC) is a relapsing inflammatory disease of unknown etiology. The increased risk of cancer in UC patients warrants for the development of novel drug treatments. Herein, this work concerns with the investigation of the protective effects of Acacia saligna butanol extract (ASBE) and its nanoformulations on UC in a rat model and its underlying mechanism. Colitis was induced by slow intrarectal infusion of 2 mL of 4% (v/v in 0.9% saline) acetic acid. Colon samples were evaluated macroscopically, microscopically, and assayed for pro-inflammatory cytokine levels. To monitor associated metabolic changes in acetic acid-induced UC model, serum samples were analyzed for primary metabolites using GC–MS followed by multivariate data analyses. Treatment with ASBE attenuated acetic acid-induced UC as revealed by reduction of colon weight, ulcer area, and ulcer index. ASBE treatment also reduced Cyclooxygenase-2 (COX-2), Prostaglandin E2 (PGE2) & Interleukin-1β (IL-1β) levels in the inflamed colon. The nano-formulation of ASBE showed better protection than the crude extract against ulcer indices, increased PGE2 production, and histopathological alterations such as intestinal mucosal lesions and inflammatory infiltration. Distinct metabolite changes were recorded in colitis rats including a decrease in oleamide and arachidonic acid along with increased levels of lactic acid, fructose, and pyroglutamic acid. Treatment with nano extract restored metabolite levels to normal and suggests that cytokine levels were regulated by nano extract in UC. Conclusion: ASBE nano extract mitigated against acetic acid-induced colitis in rats, and the underlying mechanism could be attributed to the modulatory effects of ASBE on the inflammatory cascades. The applicability of metabolomics developed in this rat model seems to be crucial for evaluating the anti-inflammatory mechanisms of new therapeutics for acute colitis.